The fallen angel [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2012)
After narrowly surviving his last operation, Gabriel Allon, the wayward son of Israeli intelligence, has taken refuge behind the walls of the Vatican, where he is restoring one of Caravaggio's greatest masterpieces.